FAKTOR-FAKTOR DETERMINAN YANG MEMPENGARUHI LOYALITAS KONSUMEN INDOMIE DI WILAYAH PROPINSI JAWA TENGAH - Dian Marhaeni K; - Trimanah, MSi (Majalah Ilmiah Sultan Agung, 2011)
The study was conducted to determine what factors are affecting the determinants of consumer loyalty in the community Indomie Central Java. The theory used is a theory about the brand and brand equity of Terrence A. Shimp. As for the analysis of the data used is descriptive quantitative analysis based on survey results analyzed in the field. The results of this study indicate that the crisis that hit the Indomie brand some time ago due to withdrawal from the market in Taiwan, had no effect on the purchasing power or the society's view of this product. They remain unaffected Indomie consumer issues as the theory presented by Jacoby and KrynerÂ  which states the brand loyalty is a behavioral response that is biased, expressed continuously by the decision-making unit with respect to one or more alternative brands of a similar brand and is a function of psychological processes.Keyword : Determinant Factor, Consumers Loyality, Indomie Consumers